Deconstructing corruption in Africa - Kubbe, Ina 1983-; Abdulai, Emmanuel Saffa ca. 20./21. Jahrhundert; Johnston, Michael 1949- (Routledge, Taylor & Francis Group, 2025)
"This book investigates corruption and anti-corruption efforts in Africa, emphasising the regional and thematic differences across the continent, whilst also exploring key patterns and trends. Combatting the ethnocentrism of Western corruption research, this book highlights the importance of a home-generated and contextualised approach to understanding corruption in Africa. Bringing together a rich array of qualitative, quantitative, and mixed methods research, the book considers how corruption manifests in a range of selected countries across the political, economic, and social spheres. The book adopts a strong comparative approach, exploring patterns, dynamics, and mechanisms in African societies. It assesses the historical underpinnings of corruption, emerging trends, and socio-economic realities before suggesting realistic contemporary solutions to the challenges of corruption in Africa. Bringing together academics and practitioners, readers will encounter intellectual discussion face-to-face with realities on the ground. As such, the book will be useful for scholars, politicians, public officials, and civil society organizations, as well as for students and researchers across the fields of political science, public administration, economy and corruption studies."
Keywords: Korruption; Afrika; Corruption / Africa / Politics and government; Corruption / Africa / Prevention; Corruption / Economic aspects / Africa; Corruption / Social aspects / Africa; Aufsatzsammlung